Additional energy scale in SmB6 at low-temperature - L. Jiao (Nature Portfolio, 2016)
Many discrepancies exist to question the nature of the candidate topological Kondo insulator, SmB6. Here, Jiao et al. observe in-gap states on well characterized (001) surfaces of SmB6, indicating a suppression of the Kondo effect at surface, which reconciles current discrepancies on this compound.